Efficacy of classification based "cognitive functional therapy" in patients with non-specific chronic low back pain - a randomized controlled trial. - Vibe Fersum, K.; O'Sullivan, Peter; Skouen, J.; Smith, Anne; Kvale, A. (John Wiley & Sons Ltd., 2013)
Background: Non-specific chronic low back pain disorders have been proven resistant to change, and there is still a lack of clear evidence for one specific treatment intervention being superior to another. Methods: This randomized controlled trial aimed to investigate the efficacy of a behavioural approach to management, classification-based cognitive functional therapy, compared with traditional manual therapy and exercise. Linear mixed models were used to estimate the group differences in treatment effects. Primary outcomes at 12-month follow-up were Oswestry Disability Index and pain intensity, measured with numeric rating scale. Inclusion criteria were as follows: age between 18 and 65 years, diagnosed with non-specific chronic low back pain for >3 months, localized pain from T12 to gluteal folds, provoked with postures, movement and activities. Oswestry Disability Index had to be >14% and pain intensity last 14 days >2/10. A total of 121 patients were randomized to either classification-based cognitive functional therapy group n = 62) or manual therapy and exercise group (n > = 59). Results: The classification-based cognitive functional therapy group displayed significantly superior outcomes to the manual therapy and exercise group, both statistically (p < 0.001) and clinically. For Oswestry Disability Index, the classification-based cognitive functional therapy group improved by 13.7 points, and the manual therapy and exercise group by 5.5 points. For pain intensity, the classification-based cognitive functional therapy improved by 3.2 points, and the manual therapy and exercise group by 1.5 points. Conclusions: The classification-based cognitive functional therapy produced superior outcomes for non-specific chronic low back pain compared with traditional manual therapy and exercise.